2008
DOI: 10.1002/ppul.20947
|View full text |Cite
|
Sign up to set email alerts
|

Swimming pool, respiratory health, and childhood asthma: Should we change our beliefs?

Abstract: Summary. Swimming is often recommended as a sport because of its several benefits to health. It is also recommended in asthmatic children as a sport with a lower potential for prompting exercise-induced asthma. However, there is growing interest in the potentially harmful effects of repeated respiratory tract exposure to chlorinated products and the problem of possible swimmingrelated health hazards is gaining importance at international level. It is already known that acute exposure to chlorine gas as in swim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 46 publications
1
56
0
1
Order By: Relevance
“…Due to the cross-sectional design of these studies, however, a healthy worker effect cannot be ruled out. Several studies have shown a higher prevalence of asthma among swimmers compared to other athletes [85], but the direction of the association is not clear, given that swimming is a recommended sport for asthmatics [85,86].…”
Section: Occupational Exposurementioning
confidence: 99%
“…Due to the cross-sectional design of these studies, however, a healthy worker effect cannot be ruled out. Several studies have shown a higher prevalence of asthma among swimmers compared to other athletes [85], but the direction of the association is not clear, given that swimming is a recommended sport for asthmatics [85,86].…”
Section: Occupational Exposurementioning
confidence: 99%
“…We have demonstrated that exposure of rats and mice to Cl 2 leads to extensive injury to airway and alveolar lung epithelia, decreased surfactant function, decreased ability of alveolar epithelial cells to actively transport sodium ions and clear fluid, and decreased levels of ascorbate and a decreased ratio of glutathione to oxidized glutathione in BAL and lung tissues (8)(9)(10). These inflammatory responses continue to induce injury after cessation of Cl 2 exposure, culminating in acute lung injury, adult respiratory distress syndrome, and reactive airway syndrome (9,(11)(12)(13)(14)(15)(16)(17). The precise mechanism of this post-Cl 2 exposure injury remains unclear and important to address because this aspect of Cl 2 -induced injury is the primary goal for therapies.…”
mentioning
confidence: 99%
“…Studies conducted in Germany (11,12), Italy (13), and Spain (14) did not find an increased risk of asthma among children attending swimming pools. Despite the conflicting results, there is agreement on the complexity of the potential role of swimming in asthma etiology and the important public health implications (1,(15)(16)(17). Asthma is among the most common chronic diseases in children (18), and swimming is one of the most practiced sports in western countries (19), where sedentarism and obesity are increasing, especially among children (20).…”
mentioning
confidence: 99%